Nutritional status assessment among medical students in Gujarat - Desai, Gaurav J.; Jadav, Pranay A.; Savsani, Priya B.; Verma, Pramod B. (International Journal Of Community Medicine And Public Health, 2019)
Background: India is facing nutrition transition. Period of college life is the phase was healthy and unhealthy diet habits takes place. The present study was aimed to study nutritional status among students of a medical college. Methods: A cross sectional study was conducted among the 254 students of a medical college attached with the civil hospital Gandhinagar over a period of six months. Pre-tested, semi-structured, self-administered questionnaire was used to collect socio-demographic information. Anthropometric examination like height, weight, BMI, waist-hip ratio was done according to WHO criteria. Data were analysed with Epi info 7. Results: Among 254 study participants, 159 (62.60%) were female and 99 (33.40%) were males. Obesity according to waist-hip ratio is significantly higher in females as compared to males Physical activities are significantly higher in females as compared to males in present study (p<0.05). Family history of diabetes and hypertension were also significantly higher in females as compared to males. Conclusions: Obesity according to Weight hip ratio was more in females as compared to male. Physical inactivity is also significantly higher in females. As per BMI undernutrition was also prevalent in the study participants.